Conversation Implications In The Disney Princess Book (al-ba??u 'an al-kanzi): A Pragmatic Overview - Purnomo, Kirana Aprilia (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
This study aims to analyze the form of speech acts and the meaning of conversational implicatures in the book Disney Princess (al-ba??u 'an al-kanzi) by Jacqueline A. Ball as a corpus of data. The data of this study used a qualitative approach with a descriptive method. The results of the research in the book show that there are three forms of speech and conversational implicatures, namely, locutionary forms, illocutions, and perlocutions. The classification of conversational implicatures with twelve locutionary speech forms, namely: seven declarative sentences, one imperative sentence, and four interrogative sentences. The 35 illocutionary forms found were a) assertive with the function of stating four utterances, proposing one utterance, complaining in one utterance, and expressing an opinion in one utterance; b) the directive with the function of commanding is two utterances, asking for four utterances, and giving advice in two utterances; c) commissive with the function of promising two utterances, and offering one utterance; d) expressive with the function of thanking ten utterances, criticizing five utterances, and praising two utterances. Meanwhile, the perlocutionary forms found were five utterances with two persuading effects, one effect of making the hearer to do something, one effect of making the hearer to think, and one effect of attracting attention.